Infección del tracto urinario por salmonella no typhi en paciente diabética - Berrospi Rojas, Carlos (2018)
Urinary tract infection is a major health problem. Urinary infection caused by a microorganism of the genus Salmonella is rare and is associated with immunosuppressive diseases. We present the case of a patient with a history of Diabetes Mellitus that presents urinary discomfort and positive urine culture to Salmonella no tiphy. With the advancement of medicine and the increase in immunosuppressive processes, this type of pathologies can be seen more frequently.